High Rates of Non-Tuberculous Mycobacteria Isolation in Mozambican Children with Presumptive Tuberculosis. - Elisa López-Varela; Alberto L García-Basteiro; Orvalho J Augusto; Oscar Fraile; Helder Bulo; Tasmiya Ira; Kizito Gondo; Jakko van Ingen; Denise Naniche; Jahit Sacarlal; Pedro L Alonso (PLoS ONE, 2017)
INTRODUCTION:Non-tuberculous mycobacteria (NTM) can cause disease which can be clinically and radiologically undistinguishable from tuberculosis (TB), posing a diagnostic and therapeutic challenge in high TB settings. We aim to describe the prevalence of NTM isolation and its clinical characteristics in children from rural Mozambique. METHODS:This study was part of a community TB incidence study in children <3 years of age. Gastric aspirate and induced sputum sampling were performed in all presumptive TB cases and processed for smear testing using fluorochrome staining and LED Microscopy, liquid and solid culture, and molecular identification by GenoType® Mycobacterium CM/AS assays. RESULTS:NTM were isolated in 26.3% (204/775) of children. The most prevalent NTM species was M. intracellulare (N = 128), followed by M. scrofulaceum (N = 35) and M. fortuitum (N = 9). Children with NTM were significantly less symptomatic and less likely to present with an abnormal chest radiograph than those with M. tuberculosis. NTM were present in 21.6% of follow-up samples and 25 children had the same species isolated from ≥2 separate samples. All were considered clinically insignificant and none received specific treatment. Children with NTM isolates had equal all cause mortality and likelihood of TB treatment as those with negative culture although they were less likely to have TB ruled out. CONCLUSIONS:NTM isolation is frequent in presumptive TB cases but was not clinically significant in this patient cohort. However, it can contribute to TB misdiagnosis. Further studies are needed to understand the epidemiology and the clinical significance of NTM in children.